Legal Mechanisms For The Formation Of An Entrepreneurial Culture Among Young People In The Context Of Reforms - Rakhmanov Abdurauf Muhammedovich (Periodica Journal, 2025)
The article focuses on the development of a culture of entrepreneurship among young people and the creation of its legal mechanisms. In consequence the concept of a culture of entrepreneurship and the factors influencing its formation has been analyzed. Furthermore, it states that within the national, spiritual and universal values in the formation of a culture of entrepreneurship among young people in the context of reforms it is exact to pay a proper attention to a moral points of the given issue concerning reforms being implemented in our country
Keywords: entrepreneurship; entrepreneurial culture; moral values